Tingkat Kandungan Histamin pada Ikan Cakalang (Katsuwonus Pelamis) dengan Metode Pembekuan yang Berbeda di CV. Novira Abadi Kota Banda Aceh - Arvatin Mawaddah; Anhar Rozi; Akbardiansyah Akbardiansyah (Publikasi Indonesia, 2023)
The fisheries sector in Indonesia has a greater potential, namely pelagic and demersal fish populations including skipjack tuna and tuna skipjack tuna are referred to as commodities that have high nutritional value but are easily damaged because they contain lots of protein which is high in free amino acids for microbial metabolism. production of ammonia, biogenic amines, organic acids, ketones and sulfur composition. Fish is one of the food products that is prone to deterioration in quality due to the action of enzymes or microbial growth. Handling of fresh fish can be done by applying cold temperatures through freezing techniques to prevent deterioration of fish quality. The SCF (semi contact plate freezer) method is a product freezing process between refrigerated shelves and this process takes place quickly. The use of semicontec in this product is fish arranged in a pan, which consists of 144 pans of cold air around the product with a temperature of - 40°C for 5 hours, with a temperature of 17.4°C in skipjack tuna, the histamine content was 0.3 ppm. ABF (Air Blast Freezer) freezing method. Freezing is done by placing the fish products that have been arranged in a pan and putting them into the ABF (air blast freezer) at the temperature used in the company, which is -35°C for 22 hours. in the arrangement of the fish that is included in the air blast freezer Freezing air blast freezer, which is a cold media made from freon that is used to freeze or ripen fish. The temperature of the fish after being frozen at air blast freezer 15.400C. by producing histamine levels in skipjack tuna 3.9 ppm, where the fish can still be consumed.